PENINGKATAN KEAMANAN KAWASAN SEHAT DENGAN ALAT PENDETEKSI KARBON MONOKSIDA BERBASISKAN MIKROKONTROLLER - Wahyuni Wahyuni; Solly Aryza; Amani Darma Tarigan; Eko Haryanto; Muhammad Isa Indrawan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This paper describes the design and means of detecting levels of carbon monoxide in healthy people, which can also provide a warning when carbon monoxide levels have exceeded normal levels. The design is carried out in several stages, including literature study, data collection, tool testing, analysis, and reporting. Carbon monoxide is a gas that cannot be felt by the human senses because it is odorless, colorless, and tasteless. The effects of carbon monoxide exposure cause poisoning and death if inhaled in certain amounts. The results of the combustion trial of each experimental substance with a maximum detection time of 10 minutes include mosquito coils with a carbon monoxide content of 31.08 Ppm, paper burning with a content of 30.46 Ppm, and cigarette smoke with the highest value of 87.63 Ppm. From the experiments conducted, it can be concluded that the design results can detect carbon monoxide levels well, this is indicated by the intensity of the levels that vary between one experimental substance and another.